Psychological capital intervention (PCI): a replication and extension - Dello Russo, S.; Stoykova P. (Human Resource Development Quarterly, 2015)
Psychological Capital (PsyCap) is a positive individual characteristic, and its malleability and openness to development have made it the focus of considerable attention in recent years. A training procedure for improving individuals’ PsyCap has been advanced and tested by Luthans and colleagues in a North American sample. The purpose of the current study was to generalize the effectiveness of the PsyCap Intervention (Luthans, Avey, Avolio, Norman, & Combs, 2006) when conducted by different trainers (i.e., replication), and to explore its longer term effects (i.e., extension). We trained a pooled sample ( N = 40) of students and professionals in Bulgaria and conducted a one-month follow-up assessment of PsyCap in order to examine the durability of the training effects. The statistical analyses revealed significant improvements in the overall PsyCap after training as well as in each of its four dimensions, namely, self-efficacy, hope, resilience, and optimism; remarkably, these improvements remained stable over one month, attesting to the durability of the training effects in the samples of both students and professionals. These results contribute to the accrual of scientific knowledge on a theory-driven and evidence-based HRD intervention.